Leveraging Biodiversity Action From Plural Values: Transformations of Governance Systems - Leventon, Julia; Duşe, Ioana A.; Horcea-Milcu, Andra-Ioana (Frontiers in Ecology and Evolution, 2021)
In this paper, we argue that leveraging plural values into action for biodiversity requires a focus on transforming the biodiversity governance system. We draw on Donella Meadows’ concept of Leverage Points, which outlines the ‘depth’ of intervention in order to shift a system towards sustainability. Engaging with deep leverage points (system intent and goals) is argued to lead to greater transformation than engaging with shallow leverage points (system design and materials). We outline how embracing plural values of biodiversity requires us to target deeper systems properties within governance systems to create space to reflect diversity in values and knowledge systems, and move away from a focus on commodification of nature’s contributions to people. We point towards understandings in political and policy sciences to highlight the known challenges in such governance system transformation. We conclude with a call for meaningful engagement with such sciences for ongoing research.